Differentials of Diarrheal Diseases Management in District Rambutan, South Sumatra, Indonesia - Rusdi Ismail (Indonesian Pediatric Society, 1995)
The aim of this report is to present the association between some sociodemographic and biomedical factors and diarrheal diseases (DD) case management practiced by the community. The study was conducted in District Rambutan, South Sumatra Province, Indonesia, based on the data from a sociodemographic survey in 1990 and sequential surveillance of DD between April 1990 and March 1991. The number of house-hold (HH) monitored was 4349 comprising 3816 children under five years of age. The point prevalence of DD in this age group was 0.007. The most prominent differentials of DD case management by the community were biomedical factors, that were duration, frequency or kind of diarrhea, and accompanying diseases. The practices of DD case attendees had been in line with the guidelines promoted by the Indonesian CDD program. But specific behaviors still deviate, which need more detail promotion guidelines and elaborate education processes based on better knowledge of the community perception, demand and which need more detail promotion guidelines and elaborate education processes based on better knowledge of the community perception, demand and practices in facing DD. Using Weiss' model, this study points out that the important determinant for these deviation is the nature of the DD itself.